Isolement et caractérisation des rhizobactéries libres et endophytes (Bacillus sp et Pseudomonas sp): Etude de leur pouvoir protecteur vis-à-vis de Fusarium oxysporum f. sp lycopersici et leur caractères liés à la promotion de la croissance des plantes. - BOUZNAD AHCENE (My University, 2016)
The plant growth promoting rhizobacteria (PGPR) are commonly inoculated to improve growth and yield of agricultural crops. They are developed to be effective plant growth promoting and successful bioconrtol agents by diverse set of traits. The present study focuses on screening of PGPR isolates showing biocontrol to phytopathogenic fungi and promotion of plants growth. 109 strains belonging to Pseudomonas and Bacillus genera have been isolated from rhizosphere and endosphere of tomato roots from Mostaganem region. Among which, 46.79% have been isolated from ectorhizospheric region, 35.78% isolated from the rhizoplane and 17.43% from the endorhizosphere. They were screened initially via their in vitro antagonistic activity against F. oxysporum f. sp lycopersici by dual culture inoculation on plate assay. 54.12% of the tested isolates demonstrated a variable inhibition rate of the phytopathogenic agent growth. The production ability of volatiles substances (HCN), siderophores and hydrolytic enzymes (pectinase, CMcellulase, protease and amylase) has also been detected. These isolates were then tested in vitro for specific PGPR traits such as the production of phosphate solubilizing enzymes, Indole Acetic Acid (IAA) and ammonia. Among the tested strains, 41% were able to solubilize the inorganic P, 69% were able to produce AIA and the all isolates were ammonia producers. Inoculation of tomato seedlings with seven different isolates has significantly enhanced seed germination, seedling vigor index, plant height, fresh weight and dry weight in comparison with control. Biocontrol activity of the seven (07) bacterial isolates has been also evaluated under greenhouse conditions. The results indicated that these Plant growthpromoting rhizobacteria (PGPR) strains provided a significant increase in shoot and root length, and shoot and root biomass over the uninoculated control. These results also indicate that the tested PGPR improved growth parameters in tomato plants and contribute towards biocontrol of the tomato wilt pathogen.
Keywords: PGPR, rhizosphere, plant promotion, biocontrol, F. oxysporum f. sp lycopersici